Proposed Method for Securing Image Using Visual Cryptography (International Journal of Engineering and Computer Science, 2015)
With the rapid growth of digital media, it is becoming more prevalent to find a method to protect the security of that media like images. An effective method for securely transmitting images is Visual Cryptography. The first algorithm in the field of Visual Cryptography was proposed in 1994 by Naor and Shamir. After this many method has develop in the field of Visual Cryptography Information. In this paper we have proposed new method for securing image. For this we have use Net Beans IDE 7. This method provides good security for image by using simple (2, 2) secret sharing scheme